CCAFS West Africa Regional Scenarios for Food Security, Environments and Livelihoods - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
From 2 to 4 November 2011 the second CCAFS scenarios development workshop was held at the hôtel Pullman Teranga in Dakar. The workshop focused on developing plausible alternate narratives of the future of West Africa in terms of socio-economic and political change and the effects of these futures on food security, environments and livelihoods. This report provides a first overview of the content generated within the workshop, encompassed by presentations, discussions in plenary and in breakout groups per day.